Toxicity of anthranilamides used in cucurbit cultivation on Apis mellifera - Costa, Ewerton Marinho da; Barros, Carlos Henrique Peixoto de; Silva, Kaique Oliveira; Mendonça, Allysson Jonhnny Torres; Cardoso, Tiago Augusto Lima; Bezerra, Carlos Eduardo Souza; Araujo , Elton Lucio de (Comunicata Scientiae, 2024)
This study aimed to evaluate the toxicity of insecticides belonging to the chemical group Anthranilamide on Apis mellifera. Toxicity was evaluated in the two experiments, which corresponded to two exposure modes: direct spraying of the products on the bees and ingestion of a contaminated diet. The two bioassays were performed in a completely randomized design composed of eight treatments (absolute control – distilled water; positive control: Thiamethoxam at 0.03 and 0.3 g.a.i. L-1; Chlorantraniliprole: 0.015 g.a.i. L-1; Cyantraniliprole: 0.05 and 0.1 g.a.i. L-1; Chlorantraniliprole + Abamectin: 0.027+0.0108 g.a.i. L-1 and 0.045+0.018 g.a.i. L-1), with 10 replications each. Via exposure through direct spraying, the insecticide Chlorantraniliprole + Abamectin, regardless of the dose used, caused 100% bee mortality, showing a TL50 of 10.05h and 8.36h for the minimum and maximum doses, respectively. The insecticide Cyantraniliprole caused the death of 33.1% and 44.9% of the bees, respectively at the minimum and maximum doses, with a TL50 of 87.79 h for the two doses. The insecticide Chlorantraniliprole showed the lowest mortality rate, 24.7%, with a TL50 of 118.88h. Via ingestion of a contaminated diet, the insecticide Chlorantraniliprole + Abamectin caused 100% mortality and showed a TL50 of 27.83h and 24.01h at the minimum and maximum doses, respectively. The insecticide Cyantraniliprole caused the death of 67.6% and 68.1% of bees at the minimum and maximum doses, respectively, with a TL50 of 58.63 h for the two doses. Chlorantraniliprole shows the lowest mortality rate, 48.1%, and a TL50 of 79.68h.